Assessing Physician‐Patient Dialogues About Chronic Migraine During Routine Office Visits. Issue 7 (4th May 2018) - Buse, Dawn C.; Gillard, Patrick; Arctander, Kaitlyn; Kuang, Amy W.; Lipton, Richard B.
Abstract : Objective: To assess physician‐patient communication and identify the frequency of use of specific communication techniques by analyzing recordings of routinely scheduled medical encounters for patients with clinician‐identified chronic migraine. Background: Chronic migraine is an under‐diagnosed, under‐treated, and highly burdensome disease. Effective medical communication is integral to optimal medical care, including providing accurate diagnoses, creating effective treatment plans, and enhancing patient adherence. Communication patterns during office visits may be a target for intervention to improve outcomes for people with chronic migraine. Design: This was a prospective, observational study based on analysis of audio recordings collected during neurologist‐patient chronic migraine dialogues. Methods: Twenty neurologists from a US neurology panel maintained by Verilogue, Inc., a research organization specializing in healthcare dialogues, were invited to identify patients with chronic migraine and record clinical encounters with their patients. Both new patient visits and follow‐up visits were included in this analysis. Neurologist‐patient dialogues were audio‐recorded, anonymized, transcribed, and analyzed by a sociolinguist for the presence of prespecified communication parameters, strategies, and specific language indicative of optimal migraine‐related medical care. Results: Fourteen out of the 20 invited neurologists (70.0%) accepted the study invitation and recorded 35 encounters with patients eligible for the study. The patient sample was 91.4% female (n = 32/35), with a mean age of 46 years. On average, there were 17 headache‐related questions per visit; 82.0% of questions were closed‐ended (n = 369/450). Headache/migraine frequency was elicited in 77.1% of the dialogues (n = 27/35), but headache days per month was assessed in only a single dialogue. Only one neurologist utilized the ask‐tell‐ask technique. Headache‐related disability was discussed in 22.9%of the dialogues (n = 8/35), with only one using open‐ended questions. None of the dialogues discussed ictal vs interictal headache‐related disability. Chronic migraine was mentioned in 8.6% of dialogues (n = 3/35) and treatment plans were discussed in 37.1% of the dialogues (n = 13/35). Conclusions: Results from this preliminary study showed that the majority of the neurologist‐chronic migraine patient dialogues did not assess elements crucial for diagnosis and treatment (eg, headache days per month and headache related disability) or use standard communication techniques (eg, open‐ended questions, ask‐tell‐ask). We recommend intervention studies designed to assess the benefits of improved communication on diagnostic accuracy, treatment decisions, and patient reported outcomes.